The Mediating Role of Worker-Occupation Fit in the Relationship Between Occupational Stress and Depression Symptoms in 1988 Medical Workers: A Cross-Sectional Study - Sun, Ruican; Lv, Keyao; He, Zirui; Liao, Liang; Wang, Hongping; Lan, Yajia (Frontiers in Public Health, 2022)
Objective: Occupational stress is generally acknowledged as a global phenomenon with significant health and economic consequences. The medical worker is a vulnerable group at a high-level risk for depressive symptoms. This study aimed to examine the mediating effect of work occupation fit (WOF) in relation to occupational stress and depressive symptoms among 1988 medical workers in China. Methods: A multi-center cross-sectional study was conducted during June and October 2020 in Henan Province, China. The participants were medical workers from four targeted hospitals (included one general and three specialized hospitals). The Depression, Anxiety, and Stress Scale (DASS-21 Scale), Worker-Occupational Fit Inventory (WOFI), as well as questions about demographic and occupational information were administered in questionnaires distributed to 1988 medical workers. Hierarchical linear regression analysis was used to examine the moderating role of work occupation fit. Results: In this study, there are 43.5% (n=864) of medical workers experienced depression symptoms. The mean score of work occupation fit was 31.6±7.1, character fit, need-supply fit and demand ability fit were 11.3±2.5, 10.1±2.7, 12.9±2.2, respectively. The occupational stress was negatively related to work occupation fit (r=-0.395, P<0.001), character fit (r=-0.529, P<0.001), need-supply fit (r=-0.500, P<0.001), and demand ability fit (r=-0.345, P<0.001). The occupational stress and depression symptoms have a positive relationship (r=0.798, P<0.001). The proportion of work occupation fit mediation was 6.5% of total effect for depression symptoms. Conclusion: Occupational stress has been identified as a risk factor for depression symptoms. Practical strategies for improving medical workers’ WOF level would help them better cope with various worker-related stressors to reduce depression symptoms. Hospital administrators could reduce medical workers’ depression symptoms by taking comprehensive measures to improve the WOF.